1995
DOI: 10.1093/ndt/10.supp3.52
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining low concentrations of plasma  2-microglobulin through continuous slow haemofiltration

Abstract: As a first step in the development of a future wearable artificial kidney, we conducted three forms of treatment with continuous haemofiltration (CHF) on a group of 10 patients in an attempt to determine what plasma values of small molecules and beta 2-microglobulin (beta 2-M) could be maintained. In the first system, one ordinary 4-h haemodialysis, followed by 7-day CHF with 51 exchange per day, was repeated. The second system consisted of CHF with 51 exchange/day and thrice weekly slow nocturnal dialysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A continuous hemofilter should maintain function for at least one week, and an artificial membrane and tubular epithelial cell‐layers should maintain tubular function for one month, if possible. We previously confirmed that 10 L/day of continuous hemofiltration enabled patients to maintain their time‐averaged concentrations of urea, creatinine, uric acid, inorganic phosphate and β 2 ‐microglobulin at lower levels than those of the patients treated with standard hemodialysis (16). Thus, as the first step towards the development of bioartificial kidneys, we intended to develop a bioartificial kidney system by which 10 L/day of filtrate could be obtained from a patient using a continuous hemofilter and 6/10 L of filtrate would be regenerated and metabolized, discarding 4 L/day by replaced by drinking and meals.…”
Section: (1) a Bioartificial Kidney Systemmentioning
confidence: 72%
“…A continuous hemofilter should maintain function for at least one week, and an artificial membrane and tubular epithelial cell‐layers should maintain tubular function for one month, if possible. We previously confirmed that 10 L/day of continuous hemofiltration enabled patients to maintain their time‐averaged concentrations of urea, creatinine, uric acid, inorganic phosphate and β 2 ‐microglobulin at lower levels than those of the patients treated with standard hemodialysis (16). Thus, as the first step towards the development of bioartificial kidneys, we intended to develop a bioartificial kidney system by which 10 L/day of filtrate could be obtained from a patient using a continuous hemofilter and 6/10 L of filtrate would be regenerated and metabolized, discarding 4 L/day by replaced by drinking and meals.…”
Section: (1) a Bioartificial Kidney Systemmentioning
confidence: 72%
“…They also used a 0.4 m 2 membrane surface area of bioartificial tubules on a dog with acute renal failure as long as 3 days (9). We previously reported that continuous slow hemofiltration therapy with a 10 L exchange per day provided low serum BUN and creatinine levels (10). In this therapy, regeneration of filtrated fluid or supply of substitution fluid was needed.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Continuous haemofiltration with 10 L (L)/day of ultrafiltrate in eight maintenance dialysis patients was evaluated for four or eight weeks by Saito et al . 10 Plasma urea nitrogen, creatinine, and uric acid levels in those patients remained at negative 60 to negative 40% of the ordinary predialysis values ( Fig. 1), plasma inorganic phosphate levels were maintained within normal limits three weeks after the start of continuous treatment, and the plasma b 2 -microglobulin level remained under 20 mg/L 4 weeks after the start of continuous treatment (Fig.…”
Section: Development Of Antithrombogenic Continuous Haemofiltration Smentioning
confidence: 92%
“…Although continuous haemofiltration was previously favoured for chronic dialysis patients, it had been tried only for short durations because of the limited antithrombogenic capability of continuous haemofilters 6–9 . Continuous haemofiltration with 10 L (L)/day of ultrafiltrate in eight maintenance dialysis patients was evaluated for four or eight weeks by Saito et al 10 . Plasma urea nitrogen, creatinine, and uric acid levels in those patients remained at negative 60 to negative 40% of the ordinary predialysis values (Fig.…”
Section: Introductionmentioning
confidence: 99%